Clinical end point definitions after percutaneous coronary intervention and their relationship to late mortality: an assessment by attributable risk. Issue 7 (30th December 2005) - Chew, D P; Bhatt, D L; Lincoff, A M; Wolski, K; Topol, E J
Abstract : Objectives: To explore the relative and absolute risks associated with various definitions for myocardial infarction, bleeding and revascularisation within the context of percutaneous coronary intervention (PCI). Methods: The REPLACE-2 (randomised evaluation of PCI linking Angiomax to reduced clinical events) database of patients undergoing PCI was used. Various definitions of myocardial infarction, bleeding and revascularisation were modelled by logistic regression assessing their relationship with 12-month mortality. Estimates from these models were used to calculate the "attributable fraction" for late mortality associated with each definition. Results: The most liberal definition of myocardial infarction was associated with an attributable risk of 13.7% (95% CI 3.4% to 23.0%). The most stringent definition was associated with an attributable risk of 4.6% (95% CI 0.6% to 8.6%). Restrictive definitions of bleeding such as TIMI (thrombolysis in myocardial infarction) major bleeding are associated with a high odds ratio of risk (6.1, 95% CI 2.1 to 17.7, p  =  0.001) but low attributable fraction (3.5%, 95% CI 0.9% to 6.8%). Conclusions: Stringent end point definitions may under-represent the clinical significance of adverse outcomes after PCI. Considering both the proportional and absolute risk associated with definitions may be a more useful method for evaluating clinical trial end points. This analysis supports the current definitions of ischaemic events but suggests that more liberal definitions of bleeding events may also be relevant to late mortality.